2013
DOI: 10.1007/s13197-013-1056-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters for obtaining surimi-like material from mechanically separated chicken meat using response surface methodology

Abstract: Surimi is a semi-processed washed fish mince protein concentrate mixed with cryoprotectants for frozen storage, which is the primary constituent of processed foods. Mechanically separated chicken meat (MSCM) is a common ingredient of comminuted sausages mainly due to its low price. The present work aimed to define the adequate parameters to obtain surimi-like material from MSCM using response surface methodology, and to characterize the chemical and textural properties of this product. The MSCM was utilized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 49 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…The frankfurter from MSCM surimi-like material presented a low lipid content compared to sausages obtained from other meat sources (TBCA-USP, 2005), mainly due the pig lard addition, once that the lipid content of the MSCM surimi-like material, obtained at the present conditions, was quite reduced (Cortez-Vega et al, 2012). Pig lard was added to the formulation to evaluate its effect on the product's texture.…”
Section: Proximate Compositionmentioning
confidence: 83%
See 2 more Smart Citations
“…The frankfurter from MSCM surimi-like material presented a low lipid content compared to sausages obtained from other meat sources (TBCA-USP, 2005), mainly due the pig lard addition, once that the lipid content of the MSCM surimi-like material, obtained at the present conditions, was quite reduced (Cortez-Vega et al, 2012). Pig lard was added to the formulation to evaluate its effect on the product's texture.…”
Section: Proximate Compositionmentioning
confidence: 83%
“…MSCM was washed in 3 cycles utilizing in each cycle a washing solution:MSCM ratio of 4 : 1 (v/w), temperature of 7 C, for 10 min (Cortez-Vega et al, 2012). In each washing cycle, the stirring was kept constant at 220 r/min using a mechanical agitator (Marconi model Piracicaba,Brazil).…”
Section: Mscm Surimi-like Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the MSCM composition varies in function of the raw material utilized (Cortez-Vega et al , 2015), a variable number of washings may be necessary to obtain surimi-like material with reduced fat contents. Here, the fat content of the MSCM-SLM was significantly reduced to 11.98% and protein increased to 83.64% (dry basis) ( p <0.05) after three washing cycles (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…No other fraction of muscle proteins and no other protein substitute used in the food industry exhibit such advantageous functional properties as myofibrillar proteins. The results of many studies clearly indicated that based on the principles of fish surimi technology, it is feasible and viable to recover from mechanically recovered poultry meat (MRPM) this technologically and nutritionally most valuable protein fraction (Yang and Froning 1994;Nowsad et al 2000;Stangierski and Kijowski 2000;Perlo et al 2006;Ramadhan et al 2011;Cortez-Vega et al 2012, 2015. The production method of fish surimi was developed and patented in Japan in the 1960s.…”
Section: Introductionmentioning
confidence: 99%